PLPKI: A novel serine protease inhibitor as a potential biochemical marker involved in horizontal resistance to Phytophthora infestans - Feldman, Mariana Laura (2014)
Potato leaves infected with Phytophthora infestans produced a serine protease inhibitor (PLPKI) with specificity for microbial proteases. Sequencing of the first twenty residues at the NH2-terminus of the mature PLPKI polypeptide demonstrated that PLPKI is a novel member of the potato protease inhibitor I family. PLPKI inhibited the activity of extracellular proteases produced by two pathogens of potato, P. infestans and Rhizoctonia solani, but was inactive against proteases secreted into the culture media by the binucleate Rhizoctonia N2, a non-pathogenic fungus for potato. Western blot analysis showed a positive correlation between the levels of PLPKI and the degree of horizontal resistance, showing its highest accumulation in clone OKA 5632.11, which has been described as highly resistant. This correlation, together with the ability of PLPKI to completely abolish the secreted serine protease activity of P. infestans, suggests that PLPKI may have an active role in protecting potato plants from this pathogenic oomycete and that it could be used as a suitable biochemical marker to help breeders in the selection of cultivars with high degree of horizontal resistance.